Design of a New Type of Shear Fork Type Chain Hoist - Jiang Haiming; Lu Jianfu; Du Jianwei (Jixie chuandong)
The improvement design for commonly used in industrial machinery hydraulic,a screw rod,a tape carrier shear fork type top up machine is carried out,making full use of rigid and flexible characteristic of chain,the chain is designed to be always rotate,another is always a rigid,through chain drive,using the special structure of the chain,the horizontal chain is transformed into vertical lift,also originally vertical chain is transformed into horizontal movement,to achieve the purpose of lifting platform. According to the characteristics of the chain,a shear fork chain hoist with the top up ascending chain as scissor is designed,and its maximum load is 20 kN,maximum stroke is 2000 mm,the maximum lifting speed is 15 m / min.